THE INFLUENCE OF BRAND IMAGE AND PRODUCT QUALITY ON CUSTOMER SATISFACTION OF STARBUCKS COFFEE MANADO - Wongkar, Cheisy Theresia; Saerang, David Paul Elia; Gunawan, Emilia Margareth (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to analyze the effect of brand image and product quality on customer satisfaction at Starbucks Coffee Manado. The approach in this study, using research with a quantitative approach and a research model using multiple linear regression analysis. Data was collected through questionnaires and literature.  The sampling technique uses purposive sampling technique, which in the implementation of this technique uses a type of non probability sampling. Respondents in this study were 92 respondents. The results showed that, 1) Simultaneously, brand image and product quality have a significant effect on customer satisfaction at Starbucks Coffee Manado. 2) Brand Image has a positive and significant effect on customer satisfaction at Starbucks Coffee Manado. 3) Product Quality has a positive and significant effect on customer satisfaction at Starbucks Coffee Manado.   Keywords: Brand Image, Product Quality, Customer Satisfaction